Correlates of Licensure Examination Performance among Marine Engineering Graduates - Montehermoso, James F. (JPAIR Multidisciplinary Research, 2009)
The purpose of this study was to determine the correlates of licensure examination performance among marine engineering graduates at John B. Lacson Foundation Maritime University -Molo, Iloilo City. This descriptive-correlational research utilizes the graduates’ transcript of records and ratings in the 4th marine engine officer licensure examination. The participants of the study were 251 examinees in the 4th marine engine officer licensure examination who were selected through simple random sampling. Frequency counts, percentages, means, and standard deviations were employed as descriptive statistics and t-test for independent samples, the One-way Analysis of Variance, the Stepwise Multiple Regression Analysis, and the Pearson’s r set at 0.05 alpha level as inferential statistics. Results showed that, generally, the marine engineering graduates of JBLFMU-Molo Inc. had "average" performance in the 4th engine officer licensure examination. Also noted was the significant differences that existed on both personal factors such as GPA in college, age upon taking the examination, year gap between graduation and board examination, and non-personal factors such as type of curriculum, categorization of graduates, type of program, and educational attainment, but no significant differences was noted on high school of origin and performance in the licensure examination.